Revealing The Meaning Of Cultural Accounting In The Safar Bath Ritual Ceremony In Bengkalis Regency - Wahyuni, Endang Sri; Sartika, Novira; Aryani, Aryani (Politeknik Negeri Bengkalis, 2024)
The purpose of this study is to find out the financing of safar bathing cultural rituals, the disclosure of cultural accountingand safar bathing traditional ceremonies as local economic and cultural values. This research is a descriptive research. Datacollection techniques use interviews, documentation and observation. The data analysis technique is with quantitative descriptiveanalysis techniques. The results of the study show that in financing the safar bathing cultural ritual as a whole, the financing comesfrom the Regional Expenditure Revenue Budget (APBD) of Bengkalis Regency. In the range of 2021 – 2023, the budget forprotection, development, material utilization, and cultural promotion activities, in this case specifically for the safar bathing culturalritual in 2021, is budgeted at IDR 159,184,000 with a realization of 92.20%, in 2022 with a realization of IDR 233,230,000 with apercentage of 94.80% while in 2023 it will increase by IDR 260,723,000 with a percentage of 90.67%. Cultural accounting refersto how cultural values influence accounting practices, including the measurement, reporting, and disclosure of financialinformation. Then the community can feel the economic value of preserving the traditions, customs, and original values of the safarbath ritual. This cultural preservation not only preserves cultural heritage, but can also bring economic benefits both directly andindirectly. The direct benefits are mainly related to the financial aspects felt by the area manager on Teluk Rhu Beach and thepeople of North Rupat village as economic and cultural actors.